(untitled) (Bangladesh Journal of Child Health, 2024)
Background: Immunoglobulin M nephropathy (IgMN) is a new clinicoimmunopathologic entity which present mainly as idiopathic nephrotic syndrome in both children and adults. The clinical manifestation of IgMN are highly variable presenting with isolated haematuria or asymptomatic proteinuria. About 6 to 23 percent of IgMN patient developed end stage kidney disease. Usually treated with immunosuppressive agents (cyclosporine/tacrolimus) along with corticosteroid has response rates up to 50%. In our institute last few years we have observed a surprisingly rise of IgM nephropathy in children. Objective: To see the response of IgMN children treated with tacrolimus or mycophenolate mofetil(MMF) and long term follow up to observe their outcome. Methodology : This was a prospective observational study done in the Department of Paediatric Nephrology, National Institute of Kidney Diseases & Urology, Dhaka, starting from January/2014 to December/2017. The study population consists of 86 IgMN children, age ranges from 2 to 12 years. The study was approved by institutional ethical review committee and informed written consent was taken from every parents. Twenty seven patients(Group-I) were selected purposively and treated with MMF and 59 patients (Group- II) treated with tacrolimus for 2 years. Patients were followed up three monthly onward in a prescribed form including adverse effect of drugs. Clinical outcome data like remission, active disease, active disease with renal impairment and dependency on renal replacement therapy(RRT) were documented for statistical analysis. Results: Of 86 IgMN children most of them were older than >8-12 years in both groups and the highest percentage were clinically diagnosed as frequently relapsing nephrotic syndrome. In Group I 43.48% children remain on remission, 13.04% have active disease, 30.43% are active disease with impaired renal function and 4.35 % went into RRT. In Group II 55.56% children remain on remission, 12.96 % have active disease, 16.67% are active disease with impaired renal function and 5.56% dependent on RRT. Conclusion: From above observations, the overall prognosis of IgMN children is not good. The clinical course and disease outcome did not differ significantly between two groups treated with mycophenolate mofetil and tacrolimus. BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 34-38